Estudo da prevalência de alterações estomatológicas e o perfil da condição de saúde bucal dos pacientes que vivem com HIV/AIDS, atendidos nas unidades de referência em São Luís – MA - CARVALHO, Célia Cristina Vieira (2008)
This study proposes to show the prevalence of oral changes in people who are living with HIV / aids who have been attending the unit of reference in Sao Luis do Maranhão, in the period April to August 2007. Furthermore, the profile was also checked the condition of oral health of these people. The main results showed that the largest number of people living with HIV / aids is male (58.6%), and most are living with the disease between one and five years. Also the majority is being followed (97.7%), receiving anti-retroviral (80.5%) three (47.5%). Only 36.7% of people who are living with HIV / aids discussed at two units of reference where the research was conducted, showed at some point some type of oral amendment, which 36.2% represents the largest number of change in form bubbles, small (61.7%), the largest percentage (53.2%) reported not feel pain. The largest percentage of examined showed need of some devzntal treatment (54.6%), while 98.4% of people examined when questioned, said brushing your teeth at least three times a day. It was found that the largest number of people living with HIV and aids by being in ambulatory monitoring shows lower prevalence in oral amendments. Those who had any injury was the biggest percentage hipercromática spots at the edge side of the tongue (33.3%) and its profile of oral health is therefore similar to that of the population that does not live with HIV and aids.